2021
DOI: 10.3390/jcm10235474
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Ischemia-Modified Albumin and Pregnancy-Associated Plasma Protein-A in COVID-19 Patients

Abstract: This study was undertaken due to the urgent need to explore reliable biomarkers for early SARS-CoV-2 infection. We performed a retrospective study analyzing the serum levels of the cardiovascular biomarkers IL-6, TNF-α, N-terminal pro-B natriuretic peptide, cardiac troponin T (cTnT), ischemia-modified albumin (IMA) and pregnancy-associated plasma protein-A (PAPP-A) in 84 patients with COVID-19.Patients were divided into three groups according to their RT-qPCR and IgG values: acute infection (n = 35), early inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…PAPP-A is a protein that is under the regulation of pro-inflammatory cytokines including IL-1 β and TNF- α [ 23 ]. A recent retrospective study of COVID-19 demonstrated elevated serum levels of PAPP-A protein in early infected patients and suggested PAPP-A as a biomarker to the early stage of COVID-19 [ 24 ]. SARS-CoV-2 study in pregnant patients and control group demonstrated no differences of PAPP-A gene expression between cohorts [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…PAPP-A is a protein that is under the regulation of pro-inflammatory cytokines including IL-1 β and TNF- α [ 23 ]. A recent retrospective study of COVID-19 demonstrated elevated serum levels of PAPP-A protein in early infected patients and suggested PAPP-A as a biomarker to the early stage of COVID-19 [ 24 ]. SARS-CoV-2 study in pregnant patients and control group demonstrated no differences of PAPP-A gene expression between cohorts [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it was stated that IMA levels were higher in the early phase of COVID-19 than in the acute phase [ 11 ]. One of the limitations of our study is that the days of the COVID-19 patients were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-modified albumin (IMA), a type of human serum albumin, where N-terminal amino acids cannot bind transition metals, is a highly sensitive marker for hypoxia [ 12 ]. Because of the absence of dyspnea and the extremely low oxygen saturation (sO 2 ) level (silent hypoxia) in COVID-19 patients, these patients are at extremely high risk, and the underlying pathomechanism is still unclear [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the absence of dyspnea and the extremely low oxygen saturation (sO 2 ) level (silent hypoxia) in COVID-19 patients, these patients are at extremely high risk, and the underlying pathomechanism is still unclear [ 13 ]. Sanchez et al observed a significant increase in IMA levels in the early period in 84 patients infected with COVID-19 [ 12 ]. This study suggests that serum IMA levels can be taken as an effective new biomarker with high sensitivity for the initial phase of COVID-19 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation